5(x+1) = 5*(x+1) = 5*x + 5*1 = 5x + 5Where does that 5 come from
I got a maths test today, but I only found out this morning that we have to learn about these, too! And I don't get the second half of this example. We're learning about Quadratic functions (well, slopes and stuff), and this is what the book's example says.
Find, in slope-intercept form, the equation of the line through (-1,3) with a slope of 5.
Then the example goes like this :
y - 3
____ = 5
x - -1
y - 3
______ = 5
x + 1
Therefore : y - 3 = 5 (x + 1)
And now, this is the part I don't get.
y + 3 = 5x + 5